Pengaruh Transparansi Laporan Keuangan, Akuntabilitas, dan Responsibilitas Pemerintah Desa terhadap Partisipasi Masyarakat dalam Pembangunan Desa di Bandung Tulungagung - Suyono, Dwi Wulan Fitriani; Pravitasari, Dyah (Shafin: Sharia Finance and Accounting Journal, 2022)
Abstract : The focus of the research is to find out how the effect of financial statement transparency, accountability, and responsibility of the village government on community participation in village development in Bandung Tulungagung. The approach used by researchers is quantitative. The data uses the primary type by distributing questionnaires to the Bandung Tulungagung village community and referring to the Likert Scale. The sample was taken by purposive sampling technique and obtained from the calculation of the Slovin formula so as to obtain 97 respondents. The data obtained were analyzed using SPSS 16.0 and tested the output of the validity test, reliability test, data normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression test, partial t test, simultaneous F test, coefficient of determination (R2). Obtaining the SPSS 16.0 test and the analysis that has been carried out shows that the transparency of financial reports, accountability, and responsibility of the village government significantly affect community participation in village development.